Preliminary Exploration of Transpedal Lymphangiography With High-Dose Ethiodized Oil Application in the Treatment of Postoperative Chylothorax - Li, Lin; Wu, Xin; Liu, Dehan; Zhang, Wei; Yang, Lian; Pan, Feng (Frontiers in Medicine, 2021)
Objective To preliminarily explore the safety and effectiveness of transpedal lymphangiography (TL) with high-dose ethiodized oil application (>20ml) in the treatment of postoperative chylothorax. Methods From 1 July 2020 to 1 July 2021, a total of 7 patients with high-flow postoperative chylothorax (>1000ml/d) were retrospectively reviewed in a single center. Clinical data, including surgery types, technical and treatment success of TL, and adverse events of TL were collected and analyzed. Results Seven patients (5 cases of non-small cell lung cancer and 2 cases of esophageal carcinoma) with a median age of 62 years (range: 30-70 years) occurred postoperative chylothorax after tumor resection with mediastinal lymphadenectomy. All patients received conservative treatment including total parenteral nutrition and somatostatin administration for a median of 20 days (range: 15-31 days) that failed to cure the chylothorax, so TL was performed as a salvage. Before TL, the median daily chyle output was 1500ml/day (range: 1100-2000ml/day). The technical success rate of TL was 100% (7/7), with the median volume of ethiodized oil of 27.6ml (range: 21.2-30.0ml) injected in TL. Ruptured thoracic duct was identified in 5 patients (5/7, 71%) in fluoroscopy and chest CT after TL. The treatment success rate of TL was 86% (6/7). In 6 patients, the thoracic drainage was removed after a median of 7 days (range: 4-13 days) from TL performance. No adverse event of TL was reported. Conclusion Transpedal lymphangiography with high-dose ethiodized oil application (>20ml) is a feasible, safe, and effective modality for the treatment of high-flow (>1000ml/day) postoperative chylothorax.